The value of debt : how to manage both sides of a balance sheet to maximize wealth - Anderson, Thomas J. (Certified investment management analyst) (Hoboken, New Jersey : Wiley, 2013)
"This book strives to develop a new vision of the value of debt in the management of individual and family wealth. Virtually every company examines both sides of its balance sheet--assets and debts--and consciously strives to achieve an optimal debt ratio. In contrast, the vast majority of individuals, wealthy or not, are either dramatically over leveraged (too much debt) or, conversely, believe that debt is always bad and should be paid off as soon as humanly possible. There are reasons, however, why practically all companies acknowledge the value of debt and seek to have an optimal debt ratio in place. As it turns out, many wealthy individuals and families--from the moderately affluent to the ultra-affluent--can also make use of similar strategies, leading to substantial long-term economic advantage. The strategic use of debt can enable individuals to become progressively wealthier by "capturing the spread" between the cost of debt and the return on investment that potentially can be generated. The use of debt can also help generate tax-free income in retirement and provide instantly available funds needed to respond to natural disasters, health crises, or personal financial difficulties. The book frames the discussion around what is an optimal debt ratio, as well as the costs, benefits and risks of implementing the strategies"--
Part 1. The value of debt in the management of wealth -- part 2. The assets-based loan facility -- part 3. Scenarios for success -- part 4. Appendixes.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance, Personal; Debt; Finance, Personal; Debt; Consumer credit; BUSINESS & ECONOMICS -- Finance; Debt; Finance, Personal; Finance, Personal; Debt; Consumer credit; Electronic books